EXACT SOLUTIONS OF THE CUBIC BOUSSINESQ AND THE COUPLED HIGGS SYSTEM - Abdelrahman, Mahmoud A. E.; Alkhidhr, Hanan A.; Baleanu, Dumitru; İnç, Mustafa (Vinca Inst Nuclear Sci, 2020)
We present explicit exact solutions of some evolution equations including cubic Boussinesq and coupled Higgs system by the unified method. The explicit solutions are expressed in terms of some elementary functions including trigonometric, exponential, and polynomial. The method is applied to a number of special test problems to test the strength of the method and computational results indicate the power and efficiency of the method.
Keywords: unified solver; solitons; elliptic functions; exact solutions; physical applications